Social influence fosters the use of a reusable takeaway box. (September 2018) - Dorn, Michael; Stöckli, Sabrina
Highlights: Severe consequences of disposable takeaway boxes call for behavioral change. Use of reusable takeaway boxes as promising solution. A field test of the role of social influence in an urban takeaway outlet. Social influence is operationalized as manipulation and observation. Choosing reusable takeaway boxes is more likely when observing it. Abstract: The severe ecological and economic consequences of disposable takeaway containers call for the implementation of effective interventions: namely, the use of reusable takeaway boxes. The present field study examined how social influence determined whether customers chose a reusable or a disposable takeaway box at a takeaway restaurant. We unobtrusively recorded the takeaway packaging choices (reusable vs. disposable) of customers over lunchtimes during a period of four weeks. We operationalized social influence in two ways. First, we manipulated social norms . For half of the field days, we added a normative message to the existing informational material on the counter of the takeaway outlet. Second, we observed social modeling by recording whether the takeaway packaging choice took place in the presence of other customers using a reusable takeaway box. The results were mixed: On one hand, we found no effect from the manipulated social norm, which we discuss in the light of past interventions using social norm messages. On the other hand, we found an effect of the observed social modeling: witnessing others using a reusable takeaway box increased the odds of choosing one oneself. This finding demonstrates the importance of getting customers to perform the desired behavior, to serve as social role models for others.